2015
DOI: 10.1080/07391102.2015.1114972
|View full text |Cite
|
Sign up to set email alerts
|

2-Deoxyglucose conjugated platinum (II) complexes for targeted therapy: design, synthesis, and antitumor activity

Abstract: Malignant neoplasms exhibit an elevated rate of glycolysis over normal cells. To target the Warburg effect, we designed a new series of 2-deoxyglucose (2-DG) conjugated platinum (II) complexes for glucose transporter 1 (GLUT1)-mediated anticancer drug delivery. The potential GLUT1 transportability of the complexes was investigated through a comparative molecular docking analysis utilizing the latest GLUT1 protein crystal structure. The key binding site for 2-DG as GLUT1's substrate was identified with molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…GLUTI1 was evaluated for its potential to transport the drug complex with the aid of comparative molecular docking analysis using the latest GLUTI crystal structure. Molecular dynamics (MD) was used in identifying the key binding site of 2-DG as a substrate for GLUTI 38. The findings from the docking result revealed that the 2-DG conjugated platinum complex can bind to the same binding site as the GLUTI substrate 38.…”
Section: New Platinum Complexes As a Product Of Drug Designmentioning
confidence: 99%
See 1 more Smart Citation
“…GLUTI1 was evaluated for its potential to transport the drug complex with the aid of comparative molecular docking analysis using the latest GLUTI crystal structure. Molecular dynamics (MD) was used in identifying the key binding site of 2-DG as a substrate for GLUTI 38. The findings from the docking result revealed that the 2-DG conjugated platinum complex can bind to the same binding site as the GLUTI substrate 38.…”
Section: New Platinum Complexes As a Product Of Drug Designmentioning
confidence: 99%
“…Molecular dynamics (MD) was used in identifying the key binding site of 2-DG as a substrate for GLUTI 38. The findings from the docking result revealed that the 2-DG conjugated platinum complex can bind to the same binding site as the GLUTI substrate 38. This led to the synthesis of the conjugate (a) and (b) and were evaluated for their cytotoxicity.…”
Section: New Platinum Complexes As a Product Of Drug Designmentioning
confidence: 99%
“…Many metal ions are indispensable for cellular functions such as respiration, redox homeostasis and gene transcription (Andreini, Bertini, Cavallaro, Holliday, & Thornton, 2008;Qian et al, 2015). However, excess metals are detrimental due to the metal catalyzed formation of hydroxyl radicals that can react with lipids, protein and DNA through Fenton reaction (Halliwell & Gutteridge, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, this histopathological behavior was exploited by a few research groups, in particular those of Gao and Lippard, who conjugated oxaliplatin to functionalized monosaccharides at different positions of the pyranose ring and tested the obtained Pt II complexes for anticancer properties with promising results.…”
Section: Introductionmentioning
confidence: 99%